Dry eye syndrome before corneal refractive surgery: the prevalence and pathogenesis-oriented therapy - N.V. Maychuk; I.S. Malyshev; M.R. Obraztsova (РМЖ "Клиническая офтальмология", 2023)
N.V. Maychuk1,2, I.S. Malyshev1, M.R. Obraztsova3 1LLC Medical Center "Hippocrates", Khimki, Russian Federation 2N.N. Burdenko Voronezh State Medical University, Voronezh, Russian Federation 3S.N. Fyodorov Eye Microsurgery Federal State Institution, Moscow, Russian Federation Aim: to assess the ocular surface in patients who were planned to undergo corneal refractive surgery (CRS), using latest diagnostic tools, and to develop a differentiated approach to the preoperative preparation of the patients with confirmed dry eye disease (DED). Patients and Methods: the study included 298 patients (298 eyes), aged 18 to 36 years, with diagnosed mild and moderate myopia, who had binocular type of vision and average keratometry readings 43.0-20.0 D. The patients were planned to undergo CRS. A standardized preoperative diagnostic examination was performed in all patients according to the protocol of refraction eye testing. The diagnostic system manufactured by MediWorks (China) was used to evaluate the ocular surface and conjunctival mucous membranes. Results: based on the results of the objective methods of examination 112 (37.6%) cases of DED were detected, including 101 (33.9%) cases of evaporative and 11 (3,7%) cases of hyposecretory forms. In addition, Schirmer-1 test was performed in patients with hyposecretory DED which showed a significantly reduced aqueous tear production. Patients with DED were advised to discontinue wearing contact lenses and to use tear substitutes containing high-molecular-weight hyaluronic acid and sodium hyaluronate in a relatively low concentration (0.15%). Also, a 0.01% solution of sulfated glycosaminoglycanes was administered to the patients. To relieve the sterile inflammatory response, the patients received a course of steroids as anti-inflammatory agents followed by cyclosporin A. An eye gel was recommended for the long-lasting overnight hydration of the corneal epithelium and its faster renewal. As a result of the positive response to the treatment, after 6–8 months of therapy it was possible to perform surgical correction in 6 (54.5%) of 11 patients of this group. In post-operative period the patients demonstrated good clinica l and functional outcomes and did not report any worsening of DED clinical signs. In 89 (88.1%) of 101 patients with evaporative DED the combination therapy consisting of the eyelid self-massage and two-phase cationic emulsion (oil-water), a mimic of tear film lipid layer, which contained the positively charged nanodrops of mineral oils dispersed in water, helped to normalize the ocular surface and tear production parameters, and thus enabled to perform CRS. Conclusion: in the group of examined patients, DED was found in 37.6% of cases, and the prevalence of evaporative form was almost 10-fold higher than that of secretory form. The occurrence of two DED forms dictates a need for the differentiated approach to diagnostics and treatment. In contrast to hyposecretory form, a clear trend to the regression of symptoms was demonstrated for evaporative form of DED, when patients received pathogenesis-oriented therapy. Thus, patients with evaporative DED clinical pattern are more likely to become candidates for CRS than those with tear hyposecretion. Keywords: dry eye syndrome, corneal refractive surgery, dysfunction of the meibomian glands, tear film, nanoemulsion. For citation: Maychuk N.V., Malyshev I.S., Obraztsova M.R. Dry eye syndrome before corneal refractive surgery: the prevalence and pathogenesis-oriented therapy. Russian Journal of Clinical Ophthalmology. 2023;23(1):14–20 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-14-20.